Nitroimidazole-based inhibitors DTP338 and DTP348 are safe for zebrafish embryos and efficiently inhibit the activity of human CA IX in Xenopus oocytes. (1st January 2018) - Aspatwar, Ashok; Becker, Holger M.; Parvathaneni, Nanda Kumar; Hammaren, Milka; Svorjova, Aleksandra; Barker, Harlan; Supuran, Claudiu T.; Dubois, Ludwig; Lambin, Philippe; Parikka, Mataleena; Parkkila, Seppo; Winum, Jean-Yves
Abstract: Carbonic anhydrase (CA) IX is a hypoxia inducible enzyme that is highly expressed in solid tumours. Therefore, it has been considered as an anticancer target using specific chemical inhibitors. The nitroimidazoles DTP338 and DTP348 have been shown to inhibit CA IX in nanomolar range in vitro and reduce extracellular acidification in hypoxia, and impair tumour growth. We screened these compounds for toxicity using zebrafish embryos and measured their in vivo effects on human CA IX in Xenopus oocytes. In the toxicity screening, the LD50 for both compounds was 3.5 mM. Neither compound showed apparent toxicity below 300 µM concentration. Above this concentration, both compounds altered the movement of zebrafish larvae. The IC50 was 0.14 ± 0.02 µM for DTP338 and 19.26 ± 1.97 µM for DTP348, suggesting that these compounds efficiently inhibit CA IX in vivo . Our results suggest that these compounds can be developed as drugs for cancer therapy.